2022
DOI: 10.1002/smll.202206314
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Perspectives of Core‐Shell Nanostructured Materials for Photocatalytic CO2 Reduction

Abstract: recombination of photogenerated charges, as well as limited catalytic reactivity and stability. [9] As a result, various approaches including constructive bandgap engineering, [10] defect engineering, [11] junction engineering, [12] and morphology control, have been proposed to enhance the photocatalytic CO 2 reduction performance. Among them, morphology control strategy could obtain multi-dimensional structures such as 0D quantum dots, 1D nanorods/nanowires, 2D nanosheets, and 3D porous/hollow structures or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 167 publications
0
16
0
Order By: Relevance
“…can be obtained, but the product rate and selectivity are very limited. Therefore, the search for a new type of co-catalyst loaded onto the surface of SiNWs to obtain photoelectrode materials with high activity and selectivity is an urgent and meaningful task in this field. Previous studies have confirmed that bimetallic systems with core–shell structures are more favorable for photogenerated electron migration and thus synergistically catalyze CO 2 RR with improved yields and selectivity. …”
Section: Introductionmentioning
confidence: 93%
“…can be obtained, but the product rate and selectivity are very limited. Therefore, the search for a new type of co-catalyst loaded onto the surface of SiNWs to obtain photoelectrode materials with high activity and selectivity is an urgent and meaningful task in this field. Previous studies have confirmed that bimetallic systems with core–shell structures are more favorable for photogenerated electron migration and thus synergistically catalyze CO 2 RR with improved yields and selectivity. …”
Section: Introductionmentioning
confidence: 93%
“…[6,7] They can also clean up the environment by photocatalytic degradation of harmful pollutants. [8][9][10] As a result, researchers have put in place various tentative to develop stable and efficient semiconductor catalysts. [11,12] In 1972, Fujishima and Honda discovered that water could be decomposed into oxygen and hydrogen by visible light at the TiO 2 electrode of an electrochemical cell without applying any external voltage.…”
Section: Introductionmentioning
confidence: 99%
“…[3] By utilizing semiconductor materials as catalysts, photocatalytic CO 2 reduction has emerged as an innovative DOI: 10.1002/adfm.202308553 green technology for converting inexhaustible solar energy into chemical energy under the background of carbonneutral. [4][5][6] Therefore, the most crucial issue for CO 2 photoreduction is the development of highly efficient and stable photocatalysts.…”
Section: Introductionmentioning
confidence: 99%